SAHA inhibits lung fibroblast activation by increasing p66Shc expression epigenetically - Yiheng Dong; Jieting Peng; Xiangyu Zhang; Qiong Wang; Xing Lyu (Aging Medicine)
Abstract Objectives To investigate the effects of suberoylanilide hydroxamic acid (SAHA) on lung fibroblast activation and to examine the role of p66Shc in this process. Methods An in vitro pulmonary fibrosis model was established using transforming growth factor‐β (TGF‐β)‐induced MRC‐5 lung fibroblasts. The proliferation and migration capacities of MRC‐5 cells, along with the expression of fibrosis‐related genes, were assessed following treatment with SAHA and/or silence of p66Shc. Results In TGF‐β‐induced MRC‐5 lung fibroblasts, SAHA treatment significantly inhibited cell proliferation and migration, as well as the expression of fibrosis‐related genes, including collagen I and α‐smooth muscle actin (SMA). Western blot and immunofluorescence assays revealed that SAHA increased p66Shc expression in both whole cells and mitochondria. Additionally, mito‐SOX assay confirmed that SAHA treatment led to a marked accumulation of mitochondrial reactive oxygen species (ROS). However, silencing of p66Shc significantly reversed the aforementioned effects of SAHA on MRC‐5 cells. Furthermore, chromatin immunoprecipitation (ChIP) assays demonstrated that SAHA enhanced active histone markers, H3K9Ac and H3K4Me3, in the p66Shc gene region. Conclusions SAHA alleviates lung fibroblast activation and migration by increasing p66Shc expression and mitochondrial ROS generation through epigenetic modifications of histone 3.